Expression of the Saccharomyces cerevisiae MPR1 gene encoding N-acetyltransferase in Zygosaccharomyces rouxii confers resistance to L-azetidine-2-carboxylate - Pribylová, L; Sychrová, H (Folia microbiologica, 2006)
The osmotolerant yeast Zygosaccharomyces rouxii is sensitive to the toxic L-proline analogue, L-azetidine-2-carboxylate (AZC). The possibility of use of the Saccharomyces cerevisiae MPR1 gene (ScMPR1) encoding the AZC-detoxifying enzyme as a dominant selection marker in Z. rouxii was examined. The heterologous expression of ScMPR1 in two Z. rouxii strains resulted in AZC-resistant colonies, but that of ScMPR1 as a dominant marker gene in vectors was affected by a high frequency of spontaneously resistant colonies. The same was found for an AZC-sensitive S. cerevisiae strain in which the ScMPR1 was expressed. In both yeasts, ScMPR1 can be used only as an auxiliary marker gene.
Keywords: Saccharomyces cerevisiae Proteins; acetyltransferasy; Culture Media; kultivační média; Acetyltransferases; technika přenosu genů; Saccharomyces cerevisiae; genetické inženýrství; kyselina azetidinkarboxylová; Selection, Genetic; genetické markery; selekce (genetika); antibiotická rezistence; Drug Resistance, Microbial; Azetidinecarboxylic Acid; Zygosaccharomyces; Saccharomyces cerevisiae - proteiny; Transformation, Bacterial; bakteriální transformace; Gene Transfer Techniques; Genetic Markers; Genetic Engineering